PERSEPSI MASYARAKAT PENGGUNA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN MANDIRI DALAM PELAYANAN RSUD LUBUK BASUNG KABUPATEN AGAM - Fitri Permata Sari; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Society health need to be considered because there are many society who complain about the services provided by the hospital when treatment specially society who use the health card (agency the social security mandiri). This research intend the first, to determine the society perception user of agency the social security mandiri health in service hospital Lubuk Basung Kabupaten Agam. Second, factors affecting service in hospital Lubuk Basung Kabupaten Agam. To analyze data obtainable from the field, this research using descriptive analysis namely to describe the phenomena that exist in the field and then interpret it according to the method, theory, techniques and those of the author with the existing repertoire literature. This research do hospital Lubuk Basung Kabupaten Agam. The results of the field showed research that society who use of agency the social security mandiri to response to the lack of services provided by the hospital Lubuk Basung starting from the timeliness service, accuracy of service, courtesy and friendliness in service, ease in getting service and convenience in service. In this research, using the theory of perception, the perception theory Notoatmodjo say perception is experience of objects, events or relationships obtainable with collect and interpret information. Perception is obtained mostly from the perceived user experience agency the social security mandiri always take medication there. This is affected by the lack of medical personnel remain, facilities work and the clarity of drug users agency the social security hospital Lubuk Basung. It is expected that the cooperation between society, hospital, agency the social security and government in realizing the quality of service.Keyword : Perception, Society, Service